Pembentukan Karakter Unggul: Analisis Optimalisasi Pendidikan Melalui Organisasi Siswa Intra Madrasah (OSIM) Di MAN 2 Deli Serdang - Yudha Wijaya Lubis (LPPM Politeknik Pratama, 2024)
This research explores the role of the Intra-School Student Organization (OSIM) in shaping student character at Madrasah Aliyah Negeri (MAN) 2 Deli Serdang, focusing on optimizing education through OSIM activities. Using qualitative research methods and case study design, the findings show that OSIM at MAN 2 Deli Serdang has a significant role in optimizing students' education. Students' participation in OSIM activities, especially the management of academic and extracurricular activities, has a positive impact on character development such as leadership, discipline, and responsibility. Nonetheless, the study identified some barriers, such as limited resources and lack of support. Therefore, efforts are needed to increase support and overcome obstacles to increase the effectiveness of OSIM in achieving the goal of superior character formation. The practical implications of this study are relevant for MAN 2 Deli Serdang and similar educational institutions, with recommendations to improve OSIM leadership training, gain further support from teaching staff, and involve parents and the community in supporting character building programs. By strengthening the role of OSIM and overcoming barriers, MAN 2 Deli Serdang can become a model in creating an educational environment that supports students' excellent character development.